Diverse crop production and profitability: Yield, economics, and labor productivity in Rangpur, Bangladesh - Md. Arifur Rahaman; Alanuzzaman Kurishi, A.S.M.; Cheesman, Stephanie; Hossain, Md. Khaled; Mani Krishna Adhikary; Parupalli, V.L. Bharathi; Md. Afzal Hossain; Hossain, Shakhawat; Ferdous, Zannatul; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
Bangladesh relies heavily on rice-based cropping systems to maintain food security. However, this dependence limits crop diversification, which is crucial for enhancing agricultural productivity and profitability in a country with high population density and limited arable land. On-farm research trials provide a brief summary of the productivity and profitability results from diversified cropping systems after one full cropping cycle. This trial was conducted in the Shibdeb and Chargonai villages of the Rangpur district, addressing food insecurity, sustainable agriculture, and climate challenges—key components for achieving TAFSSA’s goals. The trial aims to highlight the importance of crop diversification and identify strategies to increase farmers' productivity and profitability from agricultural land.